The Chameleon on the branches: spectral state transition and dips in NGC 247 ULX-1. Issue 4 (30th August 2021) - D'Aì, A; Pinto, C; Del Santo, M; Pintore, F; Soria, R; Robba, A; Ambrosi, E; Alston, W; Barret, D; Fabian, A C; Fürst, F; Kara, E; et al.
ABSTRACT: Soft Ultra-Luminous X-ray (ULXs) sources are a subclass of the ULXs that can switch from a supersoft spectral state, where most of the luminosity is emitted below 1 keV, to a soft spectral state with significant emission above 1 keV. In a few systems, dips have been observed. The mechanism behind this state transition and the dips nature are still debated. To investigate these issues, we obtained a long XMM–Newton monitoring campaign of a member of this class, NGC 247 ULX-1. We computed the hardness–intensity diagram for the whole data set and identified two different branches: the normal branch and the dipping branch, which we study with four and three hardness–intensity resolved spectra, respectively. All seven spectra are well described by two thermal components: a colder ( kT bb ∼ 0.1–0.2 keV) blackbody, interpreted as emission from the photosphere of a radiatively driven wind, and a hotter ( kT disc ∼ 0.6 keV) multicolour disc blackbody, likely due to reprocessing of radiation emitted from the innermost regions. In addition, a complex pattern of emission and absorption lines has been taken into account based on previous high-resolution spectroscopic results. We studied the evolution of spectral parameters and flux of the two thermal components along the two branches and discuss two scenarios possibly connecting the state transition and the dipping phenomenon. One is based on geometrical occultation of the emitting regions, the other invokes the onset of a propeller effect.